Problems with feminine empowerment in goddess films: A feminist analysis of South Indian goddess films - Sankaran, Chitra (Studies in South Asian Film & Media, 2014)
Abstract The goddess genre of films, popular in South India, has traditionally been conceived of as dedicated to presenting the glory and power of the Hindu goddess as divine mother, saviour and protector. The imaging of the goddess is interesting and unique in that it seems to stand outside the normal representations of women in (Indian) cinema. This has made it worthwhile to investigate this genre from the perspective of feminism. This study begins by discussing and demonstrating ways in which the goddess figure has been imaged in extra/ordinary ways to stand outside male scopic regimes. It then establishes how despite this supreme empowerment of the goddess within the filmic diegesis there is little concomitant empowerment of the mortal female. Finally, the study argues that in recent years even the empowerment of the goddess appears compromised.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTM4Ni9zYWZtLjYuMS4zXzE